Superior Performance of Microporous Aluminophosphate with LTA Topology in Solar‐Energy Storage and Heat Reallocation. Issue 11 (9th January 2017) - Krajnc, Andraž; Varlec, Jure; Mazaj, Matjaž; Ristić, Alenka; Logar, Nataša Zabukovec; Mali, Gregor
Abstract : Hydrophilic porous materials are recognized as very promising materials for water‐sorption‐based energy storage and transformation. In this study, a porous, zeolite‐like aluminophosphate with LTA (Linde Type A) topology is inspected as an energy‐storage material. The study is motivated by the material's high predicted pore volume. According to sorption and calorimetric tests, the aluminophosphate outperforms all other zeolite‐like and metal‐organic porous materials tested so far. It adsorbs water in an extremely narrow relative‐pressure interval (0.10 < p / p 0 < 0.15) and exhibits superior water uptake (0.42 g g −1 ) and energy‐storage capacity (527 kW h m −3 ). It also shows remarkable cycling stability; after 40 cycles of adsorption/desorption its capacity drops by less than 2%. Desorption temperature for this material, which is one of crucial parameters in applications, is lower from desorption temperatures of other tested materials by 10–15 °C. Furthermore, its heat‐pump performance is very high, allowing efficient cooling in demanding conditions (with cooling power up to 350 kW h m −3 even at 30 °C temperature difference between evaporator and environment). On the microscopic scale, sorption mechanism in AlPO4 ‐LTA is elucidated by X‐ray diffraction, nuclear magnetic resonance measurements, and first‐principles calculations. In this aluminophosphate, energy is stored predominately in hydrogen‐bonded network of water molecules within the pores. Abstract : High‐density storage of solar energy or waste heat is offered by a microporous aluminophosphate. Storage is based on sorption of water within the material's pores and is not prone to thermal losses. The aluminophosphate withstands repeated adsorption and desorption without degradation. It is convenient for seasonal energy storage or for the enhancement of the heat‐pump performance.